Bacterial bile salt hydrolase: an intestinal microbiome target for enhanced animal health. (3rd February 2017) - Geng, Wenjing; Lin, Jun
Abstract: To effectively mitigate antimicrobial resistance in the agricultural ecosystem, there is an increasing pressure to reduce and eliminate the use of in-feed antibiotics for growth promotion and disease prevention in food animals. However, limiting antibiotic use could compromise animal production efficiency and health. Thus, there is an urgent need to develop effective alternatives to antibiotic growth promoters (AGPs). Increasing evidence has shown that the growth-promoting effect of AGPs was highly correlated with the reduced activity of bile salt hydrolase (BSH), an intestinal bacterial enzyme that has a negative impact on host fat digestion and energy harvest; consistent with this finding, the population of Lactobacillus species, the major intestinal BSH-producer, was significantly reduced in response to AGP use. Thus, BSH is a key mechanistic microbiome target for developing novel alternatives to AGPs. Despite recent significant progress in the characterization of diverse BSH enzymes, research on BSH is still in its infancy. This review is focused on the function of BSH and its significant impacts on host physiology in human beings, laboratory animals and food animals. The gaps in BSH-based translational microbiome research for enhanced animal health are also identified and discussed.